Plan estratégico para el mejoramiento de los servicios de taxi ejecutivos de la empresa Tracktaxi s.a., cantón Quevedo periodo 2014-2017 - Alcívar Molina, Wilford Abelardo (2015)
This research was made to develop a Strategic Plan for the improvement of services executive taxi company TRACKTAXI SA Canton Quevedo. In order to provide good service to citizens. Which business problems you have in your present for this was achieved using a strategic plan to improve the service and quality was analyzed. Transportation is fundamental in the development of activities in the Canton Quevedo as in other of Ecuador several executive taxi companies were created whose purpose was to provide a "door to door" service, which guarantee; comfort and safety to users. It is noteworthy that in the Canton Quevedo inadequate enforcement of traffic law, regulations and ordinances, not met with a whole which is the problem that companies executive taxis do not have the proper organization for it was possible to make a strategic plan for executive taxi company TRACKTAXI SA.